2017
DOI: 10.1186/s12936-017-1747-6
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected selections of Plasmodium falciparum polymorphisms in previously treatment-naïve areas after monthly presumptive administration of three different anti-malarial drugs in Liberia 1976–78

Abstract: BackgroundTo assess the effect on malaria prevalence, village specific monthly administrations of pyrimethamine, chlorproguanil, chloroquine or placebo were given to children in four previously treatment-naïve Liberian villages, 1976–78. Plasmodium falciparum in vivo resistance developed to pyrimethamine only. Selection of molecular markers of P. falciparum resistance after 2 years of treatment are reported.MethodsBlood samples were collected from 191 study children in a survey in 1978. Polymorphisms in pfcrt,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Genetic polymorphisms associated with parasite resistance to chloroquine and pyrimethamine were detected in rural Liberia as early as 1978 [ 52 ]. Three decades later, resistance to chloroquine and SP continued to rise [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms associated with parasite resistance to chloroquine and pyrimethamine were detected in rural Liberia as early as 1978 [ 52 ]. Three decades later, resistance to chloroquine and SP continued to rise [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the QN sensitivities of isolates with different numbers of DNNND and NHNDHNNDDD repeats were compared [34]. Sequence polymorphisms of ms4760 in pfnhe1 have been analyzed, especially in Block II and V [41]. Studies of the association of polymorphisms in Block II and V with in vitro susceptibility to QN have shown conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the association of polymorphisms in Block II and V with in vitro susceptibility to QN have shown conflicting results. A study showed that more than one DNNND repeat in Block II and one NHNDNHNNDDD repeat in Block V in ms4760 were associated with reduced QN sensitivity in vivo [41]. The same study illustrated that isolates from Vietnam and the China-Myanmar border containing two or more DNNND repeats showed a much lower susceptibility to QN than those containing 0 or 1 repeats, and an increased number of NHNDNHNNDDD repeats was associated with high QN susceptibility in vitro [33, 42].…”
Section: Discussionmentioning
confidence: 99%
“…The global distribution of SNPs is variable, with some positions being widely distributed, like the frequently linked Y191H/A437S ( Mu et al, 2003 ; Ursing et al, 2006 ; Pirahmadi et al, 2013 ), as well as I876V ( Dahlstrom et al, 2009 ; Gupta et al, 2014 ; Zhao et al, 2019 ; Al-Ruhmi et al, 2020 ), which seems to have been circulating at least since pre-chloroquine times ( de Dios et al, 2019 ). Others are clustered in some regions, like the 1466 position, frequent in East Africa ( Dahlstrom et al, 2009 ; 2009a ), but rare in the Western coast ( Otienoburu et al, 2016 ; Jovel et al, 2017 ), and found absent in studies in Asia ( Veiga et al, 2011 ; Gupta et al, 2014 ; Phompradit et al, 2014 ) as well as in the Americas ( Dahlstrom et al, 2009 ). Pfmrp1 gene copy number variation has been observed in vitro ( Bopp et al, 2013 ) and is also likely to exist in the field, as recently suggested through deep analysis of next generation sequencing archive data from West African parasites ( Yini et al, 2018 ).…”
Section: Sequence Diversitymentioning
confidence: 99%